Edible Bird’s Nest: The Functional Values of the Prized Animal-Based Bioproduct From Southeast Asia–A Review - Lee, Ting Hun; Wani, Waseem A.; Lee, Chia Hau; Cheng, Kian Kai; Shreaz, Sheikh; Wong, Syieluing; Hamdan, Norfadilah; Azmi, Nurul Alia (Frontiers in Pharmacology, 2021)
Edible Bird's Nest (EBN) is the most prized health delicacy amongst the Chinese population in the world. Although some scientific characterization and its bioactivities have been studied and researched, no lights have been shed on its actual composition or mechanism. The aim of this review paper is to address the advances of EBN as a therapeutic animal bioproduct, challenges and future perspectives of research involving EBN. The methodology of this review primarily involved a thorough search from the literature undertaken on Web of Science (WoS) using the keyword “edible bird nest”. Other information were obtained from the field/market in Malaysia, one of the largest EBN-producing countries. This article collects and describes the publications related to EBN and its therapeutic with diverse functional values. EBN extracts display anti-aging effects, inhibition of influenza virus infection, alternative traditional medicine in athletes and cancer patients, corneal wound healing effects, stimulation of proliferation of human adipose-derived stem cells, potentiate of mitogenic response, epidermal growth factor-like activities, enhancement of bone strength and dermal thickness, eye care, neuroprotective and antioxidant effects. In-depth literature study based on scientific findings were carried out on EBN and its properties. More importantly, the future direction of EBN in research and development as health-promoting ingredients in food and the potential treatment of certain diseases have been outlined.